2011
DOI: 10.3758/s13421-011-0125-9
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the role of emotion during the search process in free recall

Abstract: Typically, research has shown that emotional words are remembered better than neutral words; however, most studies have reported only the mean proportion of correctly recalled words. The present study looked at various dependent measures used by search models to determine whether emotion can influence the search process as well. The results from Experiment 2 showed that when emotionality was made salient, participants were able to utilize emotional associations, in addition to temporal associations, to cue ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 37 publications
5
34
1
Order By: Relevance
“…Existing research has provided conflicting evidence as to whether emotion enhances (Doerksen & Shimamura, 2001) or impairs (Kensinger, 2009; Maddock & Frein, 2009; Madan et al, 2012) associative memory. Furthermore, a related study on the organizational effects of emotion on memory (Siddiqui & Unsworth, 2011) showed emotional clustering only when a valence orienting task (pleasantness judgment) was used. Together, these results suggest that a large percentage of emotional items might create subjective and variable strategies, which may interfere with the associative mechanisms that support emotional clustering.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing research has provided conflicting evidence as to whether emotion enhances (Doerksen & Shimamura, 2001) or impairs (Kensinger, 2009; Maddock & Frein, 2009; Madan et al, 2012) associative memory. Furthermore, a related study on the organizational effects of emotion on memory (Siddiqui & Unsworth, 2011) showed emotional clustering only when a valence orienting task (pleasantness judgment) was used. Together, these results suggest that a large percentage of emotional items might create subjective and variable strategies, which may interfere with the associative mechanisms that support emotional clustering.…”
Section: Resultsmentioning
confidence: 99%
“…Such an “emotional” clustering effect falls naturally out of retrieved context theories (Howard & Kahana, 2002) and is in line with other clustering phenomena, whereby individuals organize their memories by semantic, episodic and spatial associations (Bousfield, 1953; Kahana, 1996; Miller et al, 2013). Previous work has suggested that emotional clustering only occurs when participants are explicitly oriented to the emotionality of items (Siddiqui & Unsworth, 2011); however, the use of many emotional items may have altered participants’ strategies and interfered with a context mechanism. Alternatively, if emotional features are not represented in context, then there should be no consecutive recall of emotional items.…”
Section: Introductionmentioning
confidence: 99%
“…Although emotional words (typically selected to vary in both valence and arousal; e.g., Siddiqui & Unsworth, 2011;Talmi & Moscovitch, 2004;Zimmerman & Kelley, 2010; but see Kensinger & Corkin, 2003 are often recalled better than neutral words, such findings are usually observed with discrete-level versions of the mixed-list design, in which a study list contains only two or three types of items, and emotional words have the opportunity to stand out from the neutral words (Talmi, 2013). When the influences of distinctiveness and organization are controlled at study by presenting pure lists of emotional and neutral words (rather than mixed lists), and/or when the neutral comparison words are semantically related, and thus themselves categorically related, the recall benefit for emotional words is eliminated (Dewhurst & Parry, 2000;Talmi & Moscovitch, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These two factors are the primary factors used by researchers to characterize emotional words and to differentiate lists of emotional words from lists of neutral words. However, with notable exceptions in the work of Kensinger andcolleagues (e.g., Kensinger &Corkin, 2003, 2004), they have frequently been confounded in memory and metamemory research: Emotional words in many studies differ from neutral words in having both more extreme valence (i.e., more negative or more positive) and higher arousal (e.g., Siddiqui & Unsworth, 2011;Talmi & Moscovitch, 2004), including in the metamemory studies by Zimmerman and Kelley (2010) and Tauber and Dunlosky (2012).…”
Section: Dimensions Of Emotionalitymentioning
confidence: 99%
“…The fact that the backgrounds sometimes were more likely to be accessed when emotional items were cues than when neutral items were cues is particularly surprising based on prior narrowed-encoding theories. However, this enhancement may arise because the emotion-based neural network elicited by the negative and positive item cues may enhance retrieval processes, which may boost the recall rates for the associated backgrounds above the level demonstrated following a neutral item cue (Daselaar, et al, 2008; Siddiqui & Unsworth, 2011). These results reveal boundary conditions for the trade-off and demonstrate that sometimes, emotion can facilitate both object and contextual memory.…”
Section: Discussionmentioning
confidence: 99%